Generalized golden sections and a new approach to the geometric definition of a number - Stakhov, A. P. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We consider applications of generalized golden sections to the geometric definition of a number and establish new properties of natural numbers that follow from this approach.